Between us : how cultures create emotions - Mesquita, Batja (W.W. Norton, 2022)
Apioneer of cultural psychology argues that emotions are not innate, but made as we live our lives together. "How are you feeling today?" We may think of emotions as universal responses, felt inside. Using decades-long, cutting-edge research, acclaimed psychologist Batja Mesquita asks us to reconsider emotions through the lens of what they do in our relationships, both one-on-one and within larger social networks. From an outside-in perspective, readers will understand why pride in a Dutch context does not translate well to North Carolina, or why one's anger at a boss does not mean the same as your anger to a partner in a close relationship. By looking outward at relationships at work, school, and home, we can better judge how our emotions will be understood, how they might change a situation, and how they change us. Brilliantly synthesizing original psychological studies and stories from peoples across time and geography, Between Us skillfully argues that acknowledging differences in emotions allows us to find common ground, humanizing and humbling us all for the better
Keywords: etnopsychologie; emoce; ethnopsychology; emotions; monografie; monographs